ASSESSMENT OF THE WASHING MACHINES SOUND QUALITY BY THE BINAURAL MEASUREMENT SYSTEMS - Moravec, Marek; Liptai, Pavol; Zbojovský, Ján; Badidová, Anna (Технічні науки та технології, 2021)
The target and goal of psychoacoustics is to understand how people perceive and experience different sounds. Psychoacoustic is joining the field of acoustic and psychology. Sound quality is a perceptual reaction to the sound that reflects the listener’s reaction.